Future Prospects for the Natural Gas Industry in Iraq and Investment Opportunities - زيارة, رحيم حسوني; محمد, نغم عبد الحسين (Journal of Economics and Administrative Sciences, 2016)
Abstract  Natural gas is characterized by features that made from it a fuel and a raw material for many industries. Deepening its position as a favorite fossil supplier between other types of fossil fuel is the efficiency, diversity of its uses, low costs and compatibility with the environment which leads to increasing of its uses then increased global demand. So, the natural gas must take its place as an important resource in Iraq and participate the oil in the economic development process of building and financing of the general budget.  Iraq is planning to continue of increasing the export capacity of raw oil to meet ambitious production targets emanating from the main objective of the national policy of oil and of maximizing revenue within the oil licensing rounds. So, it is expected to increase the amount of gas supplied in the future. If the best exploitation for this resource is wanted, the right environment must be created especially if the production of fields of free gas which contracted in the third licensing round see light, so, the production of this wealth will be an active role in meeting the country's needs and supplement the general budget, thus alleviating the burden of lower oil prices.  This paper is focuses on the demonstration for natural gas and its uses and its characteristics and the global demand on it until the year 2035. Also, it focuses on the licenses rounds and their role in increasing the associatedgas production with the increase in oil production and gives a vision of the potential developments for these quantities until the year 2035.  The research found out that the weakness of domestic consumption of natural gas will lead to the availability of large qualify amounts for export if the construction of a social and economic system is completed to be able to exploit it the best exploitation. the best exploitation can be done through economic elements that Iraq is owned which make its land as incubator for major investment operations of natural gas by guiding the investment to rich places of the components of the success of this process, a southern region, Basra in particular, and that it is possible to achieve a successful investment opportunities